Temperature and elevated CO2 alter soybean seed yield and quality, exhibiting transgenerational effects on seedling emergence and vigor - Thenveettil, Naflath; Bheemanahalli, Raju; Reddy, Krishna N.; Gao, Wei; Reddy, K. Raja (Frontiers in Plant Science, 2024)
Environmental conditions play a prime role in the reproductive performance of plants, and they can extend into progenies. A study was conducted to examine the effect of temperature (22/14°C (low), 30/22°C (optimum), and 38/30°C (high)), and CO2 (420 ppm (ambient; aCO2) and 720 ppm (elevated; eCO2)) on seed yield, quality, and transgenerational seedling vigor traits of soybean cultivars (DS25-1 and DS31-243). A significant temperature effect was recorded among yield and quality attributes. At high-temperature treatment, the 100-seed weights of DS25-1 and DS31-243 declined by 40% and 24%, respectively, over the optimum temperature at aCO2. In both cultivars, the high temperature decreased the harvest index by 70% under both aCO2 and eCO2, compared to the optimum temperature at aCO2. High temperature increased the protein content by 8% and decreased the oil content by 2% over optimum under aCO2. Maximum sucrose (7.5%) and stachyose (3.8%) accumulation were observed at low temperatures and eCO2. The linoleic and linolenic acids decreased by 28% and 43% upon an increase in temperature from optimum to high temperature under aCO2. However, high temperature upregulated oleic acid accumulation by 63% compared to optimum temperature. Significant temperature and CO2 effects were observed in progenies with the highest maximum seedling emergence (80%), lesser time to 50% emergence (5.5 days), and higher seedling vigor from parents grown at low-temperature treatment under eCO2. Our findings suggest that parental stress can have a significant impact on the development of offspring. This indicates that epigenetic regulation or memory repose may be at play.